Development of an Android-Based Sign Language Education Game Using a Scrum-Game Approach - Imam Fauzy Muldani Rachmat; Gazali Gazali (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2021)
Sign language is used as a communication tool for deaf children. It is also used by non-disabled as a way of communicating with them. However, not all non-disabled understand sign language since knowledge of sign language is required. Based on interviews among non-disabled and deaf people, including relatives and teachers, they experience miscommunication due to the lack of communication skills using sign language and rely only on lip movements. Sign language is applied to a subject in the State Special School of Banjar City, consisting of BISINDO and SIBI with conventional learning. This research to produce game products for learning sign language can help deaf children learn sign language in schools, especially non-disabled who want to learn sign language. The method used for developing games sign language education uses the SCRUM-Game approach, UML models, BlackBox testing, and usability testing. The sprint iteration consists of two sprints that produce educational sign language games: Alphabet SIBI and BISINDO. Educational game testing uses BlackBox testing with the conclusion that all functionality valid. Usability testing of student deaf responders and non-disabled respondents for efficiency, memorability, and errors is categorized as good. Aspect satisfaction and learnability get an excellent score. Overall, the resulting educational games get a good score. Therefore it is proper to be used.